Lıngual Orthodontıcs And Aesthetıcs - Cem Canikoğlu; Yıldız Öztürk (Galenos Yayinevi, 2003)
Aesthetics has become an important aspect in the practice of modern dentistry because the smile is one of the most important facial expression and a beautiful smile is a critical component of the attractiveness. After the development of the straight wire appliance, treatment demands among adult patients have increased. Aesthetics was then a primary concern of the profession. To adress these aesthetic concern manufactures introduced clear brackets and during the early 1970 Dr. Craven Kurz, an orthodontist then assistant professor of occlusion and gnathology at University of California, School of Dentistry developed the first lingual appliance. The appliance consisted of plastic brackets bonded to the lingual aspect of the anterior dentition and metal brackets bonded to the lingual aspect of the posterior dention. Dr. Kurz in conjuction with his colleague Dr. Jim Mullick processed to develop some prototypes of lingual brackets. The main problem was a high bonding failure rate due to the shearing forces and patient discomfort from the roughness against the tongue. With the addition of an anterior inclined plane to the maxillary anterior brackets 7th generation lingual bracket was created. During fixed orthodontic treatment in some cases a combination of lingual and labial intraoral force application can be necessary. As the appearence is the most important factor for adult patients some auxiliary components used for the application of the labial orthodontic forces and for the preventation of the anchorage loss in lingual orthodontic patients will be presented in this study.